Is students' Accounting Employability Influenced by Work Integrated Learning and Networking Behavior? - Saputri, Fadhilah Mahanani; Siswandari, Siswandari; Setyowibowo, Feri (Dinamika Pendidikan, 2023)
Accounting employability skills for accounting vocational graduates include general skills, technical skills, and general knowledge, so that graduates have eligibility in the accounting field. The condition of accounting employability skills still tends to be low so that the availability of graduates in the world of work is still not optimal. This study aims to examine the effect of work-integrated learning on accounting employability skills through networking behavior. The research population was all accounting students in Klaten Regency, totaling 835 students. The sample technique used was purposive sampling with a sample size of 387 students. The test results show that work integrated learning affects accounting employability skills, networking behavior affects accounting employability skills, and work integrated learning indirectly affects accounting employability skills through networking behavior. The results show that students' practical experience in the vocational curriculum has an impact on networking behavior to stay connected to the world of work, which ultimately increases students' employability. The results of this study provide recommendations to the government as a policy maker to improve the quality of learning that is integrated with the world of work so that it has a long-term impact on improving the quality of student employment.